200 likes | 227 Views
This educational text explores logical methods to prove set identities, including using membership and truth tables, propositional logic conversions, and applying set identities. It covers key principles such as intersection, union, and complement, demonstrating logical arguments for set equalities.
E N D
Proving Things About Sets Rosen 1.6
Approaches to Proofs • Membership tables (similar to truth tables) • Convert to a problem in propositional logic, prove, then convert back • Use set identities for a tabular proof (similar to what we did for the propositional logic examples but using set identities) • Do a logical (sentence-type) argument (similar to what we did for the number theory examples)
Prove (AB) (AB) = B A B (AB) (AB) (AB)(AB) 1 1 1 0 1 1 0 0 0 0 0 1 0 1 1 0 0 0 0 0
Prove (AB) (AB) = B (AB) (AB) = {x | x(AB)(AB)} Set builder notation = {x | x(AB) x(AB)} Def of = {x | (xA xB) (xA xB)} Def of x2 and Def of complement = {x | (xB xA ) (xB xA )} Commutative x2 = {x | (xB (xA xA )} Distributive = {x | (xB T } Or tautology = {x | (xB } Identity = B Set Builder notation
A Ø = A AU = A AU = U A Ø = Ø AA = A A A = A (A) = A Identity Laws Domination Laws Idempotent Laws Complementation Law Set Identities (Rosen, p. 89)
A B = B A A B = B A A(BC) = (AB)C A(BC) = (AB)C A(BC)=(AB)(AC) A(BC)=(AB)(AC) A B = A B A B = A B Commutative Laws Associative Laws Distributive Laws De Morgan’s Laws Set Identities (cont.)
Prove (AB) (AB) = B (AB) (AB) = (BA) (BA) Commutative Law x2 =B (A A) Distributive Law =B U Definition of U =B Identity Law
Prove (AB) (AB) = B Proof: We must show that (AB) (AB) B and that B (AB) (AB) . First we will show that (AB) (AB) B. Let e be an arbitrary element of (AB) (AB). Then either e (AB) or e (AB). If e (AB), then eB and eA. If e (AB), then eB and eA. In either case e B.
Prove (AB) (AB) = B Now we will show that B (AB) (AB). Let e be an arbitrary element of B. Then either e AB or e AB. Since e is in one or the other, then e (AB) (AB).
Prove AB A Proof: We must show that any element in AB is also in A. Let e be an element in AB. Since e is in the intersection of A and B, then e must be an element of A and e must be an element of B. Therefore e is in A.
AA = (AA) - (AA) = (A) - (A) = Ø Definition of Idempotent Laws Definition of - Prove AA =
Prove A B = AB Proof: To show that A B = AB we must show that A B AB and AB AB. First we will show that A B AB. Let e A B. We must show that e is also AB. Since e AB, then e AB. So either eA or eB. If eA then eA. If eB then eB. In either case eAB
DeMorgan Proof (cont.) Next we will show that AB AB. Let e AB. Then e A or e B. Therefore, by definition e A or e B. Therefore e (AB) which implies that e AB Since A B AB and AB AB then A B = AB.
Prove A(BC)=(AB)(AC) Proof: To show that A(BC)=(AB)(AC) we must show that A(BC) (AB)(AC) and (AB)(AC) A(BC).
Distributive Proof (cont.) First we will show that A(BC) (AB)(AC). Let e be an arbitrary element of A(BC). Then e A and e (BC). Since e (BC), then either eB or eC or e is an element of both. Since e is in A and must be in at least one of B or C then e is an element of at least one of (AB) or (AC). Therefore e must be in the union of (AB) and (AC).
Distributive Proof (cont.) Next we will show that (AB)(AC) A(BC). Let x (AB)(AC). Then either x(AB) or x(AC) or x is in both. If x is in (AB), then xA and xB If xB, then x(BC). Therefore x A(BC). By a similar argument if x(AC) then, again, x A(BC). Since A(BC) (AB)(AC) and (AB)(AC) A(BC), then A(BC) = (AB)(AC).
Prove: [AB AB] [A = B] Proof: We must show that when AB AB is true then A=B is true. (Proof by contradiction) Assume that AB AB is true but AB. If AB then this means that either xA but xB, or xB but xA. If xA but xB, then x AB but x AB so AB is not a subset of AB and we have a contradiction to our original assumption. By a similar argument AB is not a subset of AB if xB but xA. Therefore [AB AB] [A = B].
Prove or Disprove [AB=AC] [B=C] False! A= Ø, B={a}, C={b} [AB=AC] [B=C] False! A={a}, B= Ø, C={a}
Prove: A (B-A) = AB Proof: We must show that A(B-A) AB and AB A (B-A). First we will show that A(B-A) AB. Let e A(B-A). Then either eA or e (B-A). If eA, then e AB. Note that e cannot be an element of both by the definition of (B-A). If e (B-A), then eB and e A by the definition of (B-A). In this case, too, e AB. Thus A(B-A) AB.
Prove: A (B-A) = AB (cont.) Next we will show that AB A(B-A). Let e AB. Then either eA or eB or both. If eA or both, then e A(B-A). The other case is eB, eA. In this case e (B-A) by the definition of (B-A). Again, this means that e A(B-A). Thus AB A(B-A). Therefore A(B-A) = AB.